Health-related quality of life, mental health and caregiver burden in children with autosomal recessive polycystic kidney disease - Gimpel, Charlotte; Schäfer, Susanne; Schaefer, Franz (Pediatric nephrology, 2026)
Pediatric chronic kidney disease (CKD) causes significantly impaired health-related quality of life (hrQOL) and caregiver burden, but no studies focus specifically on autosomal recessive polycystic kidney disease (ARPKD).
Veröffentlicht: 18 September 2025
Gesehen am 16.01.2026